Attribution of contrasting warm-season convective boundary layer height trends over the Tianshan-Taklamakan-Oasis region to thermodynamic and moisture drivers - Shi, Han; Long, Yanfei; Luo, Chao; Wu, Sijiang; Wang, Zhengbo; Guo, Wenbei; Wu, Jianxun (Frontiers in Climate, 2025)
The convective boundary layer height (CBLH) plays a crucial role in regulating atmospheric mixing and land-atmosphere interactions, yet its spatiotemporal variability in the arid, topographically complex Xinjiang region of northwestern China remains insufficiently understood. Using ERA5-Land reanalysis (1985–2024 for CBLH; 2000–2024 for driving factors) and GLASS LAI data for April–September, CBLH characteristics and trends were investigated through the Mann–Kendall test, Theil–Sen slope estimation, multiple linear regression (MLR), and principal component analysis (PCA). Results show that the Tarim and Junggar Basins exhibit higher CBLH than the surrounding mountains, with seasonal peaks in June–July. From 2000 to 2024, a significant CBLH increase occurred in the Tianshan Mountains during July, while a marked decline was observed over the Taklamakan Desert in August. MLR results indicate that August CBLH over the Taklamakan is enhanced by strong surface heating but constrained by the cooling and moistening effects of nearby oases. In contrast, July CBLH over the Tianshan is amplified by local heating and winds, yet suppressed by both local and remote moisture inputs and sensible heat flux anomalies. PCA further supports these findings, linking the Tianshan's July increases to reduced net longwave cooling, stronger sensible heating, and lower atmospheric pressure, and the Taklamakan's August decreases to enhanced cooling, weakened heating, and increased humidity. These results highlight the region's divergent CBLH responses to local forcing and cross-regional interactions, emphasizing that both warming-induced increases and moisture-driven declines must be considered in future regional climate assessments.